Analysis of Genetic and Non-genetic Predictors of Levodopa Induced Dyskinesia in Parkinson’s Disease - Tirozzi, Alfonsina; Modugno, Nicola; Palomba, Nicole Piera; Ferese, Rosangela; Lombardi, Alessia; Olivola, Enrica; Gialluisi, Alessandro; Esposito, Teresa (Frontiers in Pharmacology, 2021)
Background: Levodopa (L-Dopa), representing the therapeutic gold standard for the treatment of Parkinson Disease (PD), is associated with side effects like L-Dopa induced dyskinesia (LID). Although several non-genetic and genetic factors have been investigated for association with LID risk, contrasting results were reported and its genetic basis remain largely unexplored. Methods: In an Italian PD cohort (N=460), we first performed stepwise multivariable Cox Proportional Hazard regressions modelling LID risk as a function of gender, PD familiarity, clinical subtype, weight, age-at-onset (AAO) and years-of-disease (YOD), L-Dopa dosage, severity scores, and scales assessing motor (UPDRS-III), cognitive (MoCA), and non-motor symptoms (NMS). Then we enriched the resulting model testing two variants - rs356219 and D4S3481 - increasing the expression of the SNCA gene, previously suggested as a potential mechanism of LID onset. To account for more complex (non-linear) relations of these variables with LID risk, we built a survival random forest (SRF) algorithm including all the covariates mentioned above. Results: Among tested variables (N=460 case-complete, 211 LID events; total follow-up 31,361 person-months, median 61 months), disease duration showed significant association (p<0.005), with 6(3-8)% decrease of LID risk per additional YOD. Other nominally significant associations were observed for gender - with women showing a 39(5-82)% higher risk of LID – and AAO, with 2(0.3-3)% decrease of risk for each year increase of PD onset. The SRF algorithm confirmed YOD as the most prominent feature influencing LID risk, with a variable importance of about 8% in the model. In genetic models, no statistically significant effects on incident LID risk was observed. Conclusions: This evidence supports a protective effect of late PD onset and gender (men) against LID risk and suggests a new independent protective factor, YOD. Moreover, it underlines the importance of personalized therapeutic protocols for PD patients in the future.